First experimental results on active and slim-edge silicon sensors for XFEL. (12th December 2016) - Pancheri, L.; Benkechcache, M. E. A.; Betta, G.-F. Dalla; Xu, H.; Verzellesi, G.; Ronchin, S.; Boscardin, M.; Ratti, L.; Grassi, M.; Lodola, L.; Malcovati, P.; Vacchi, C.; et al.
Abstract: This work presents the first characterization results obtained on a pilot fabrication run of planar sensors, tailored for X-ray imaging applications at FELs, developed in the framework of INFN project PixFEL. Active and slim-edge p-on-n sensors are fabricated on n-type high-resistivity silicon with 450 μ m thickness, bonded to a support wafer. Both diodes and pixelated sensors with a pitch of 110 μ m are included in the design. Edge structures with different number of guard rings are designed to comply with the large bias voltage required by the application after accumulating an ionizing radiation dose as large as 1GGy. Preliminary results from the electrical characterization of the produced sensors, providing a first assessment of the proposed approach, are discussed. A functional characterization of the sensors with a pulsed infrared laser is also presented, demonstrating the validity of slim-edge configurations.